IMPLEMENTASI MANAJEMEN PENDIDIKAN BERBASIS KARAKTER DI SEKOLAH - Colle Said (Paedagogia: Jurnal Pendidikan, 2019)
Character-based education management aims to integrate everything, both personal, spiritual, attitudes and behaviors as well as material related to the achievement of educational goals. In the process, education of all the efforts of the people involved in the process of achieving these educational goals is then effectively integrated, organized and coordinated, and all materials needed, and existing ones are used efficiently. Character-based education management in schools can be as a basic knowledge that has its own characteristics that are different from other administrative sciences that lie in its operational principles, and not in general principles. Every activity in the education administration process is directed to achieve educational goals. In the management of character-based education, it is also necessary to have good coordination and supervision or supervision from the leadership. Keywords: